THE CORE-OBLIQUE DISTINCTION IN SOME AUSTRONESIAN LANGUAGES OF INDONESIA AND BEYOND - I. Wayan Arka (SCOPUS ID: 8955319100) (Masyarakat Linguistik Indonesia, 2017)
This paper explores the nature of core-oblique distinctions in some Austronesian languages of Indonesia, focusing on the intermediate status between core and oblique categories. It proposes a core index, a novel method to determine the core status of an argument. Core index evidence shows that there is a cline running from syntactically core to non-core (oblique), and that the degree of coreness in Indonesian and Balinese shows striking parallelism. The proposed core-index-based analysis allows us to claim syntactic transitivity with confidence and to resolve successfully the controversial transitivity problem of the Indonesian bare verb construction. The analysis advances our understanding of the nature of semi-core arguments, syntactic transitivity, symmetricality of voice system, and alternative argument realisations, not only in Indonesian and Balinese, but also in other typologically different Austronesian languages of central and eastern Indonesia and beyond. Importantly, the core-index study also provides a means for cross-linguistic comparative analysis of the unusual alternative pattern of applicativisation whereby no core promotion is involved. The paper also discusses how the gradient nature of the core-oblique distinction, particularly semi-coreness of arguments, poses a challenge for any theory that posits discrete classes of relations.